2003
DOI: 10.1002/pssb.200303262
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of InGaN/GaN single quantum wells by X‐ray scattering and transmission electron microscopy

Abstract: A set of In x Ga 1-x N/GaN single quantum wells (SQWs) were analysed using X-ray reflectivity (XRR), high resolution X-ray diffraction (HRXRD) and high resolution transmission electron microscopy (HRTEM). A method for determining the thickness and composition of the single quantum well layers using only X-ray scattering measurements is described -the results agree very closely with those determined from HRTEM analysis of the same samples. HRTEM lattice fringe images obtained from InGaN subjected to minimal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 8 publications
1
37
0
Order By: Relevance
“…At low electron dose, the lattice fringe image of the quantum well and the lattice parameter map are both reasonably uniform ( figure 1a, 1c), [16,17]. We have studied the effect of 200, 300, and 400 keV incident electrons.…”
Section: Transmission Electron Microscopymentioning
confidence: 97%
See 4 more Smart Citations
“…At low electron dose, the lattice fringe image of the quantum well and the lattice parameter map are both reasonably uniform ( figure 1a, 1c), [16,17]. We have studied the effect of 200, 300, and 400 keV incident electrons.…”
Section: Transmission Electron Microscopymentioning
confidence: 97%
“…In the light of the Smeeton et al [16,17] papers, which suggested that the gross indium-rich clusters in InGaN quantum wells reported by many researchers might be due to electron beam damage, the Gerthsen group revised their earlier conclusions [11,12]. They observed that the indium concentration in the clusters increased with increasing irradiation time in the electron microscope.…”
Section: Does Tem Give Any Evidence For Genuine In Clustering?mentioning
confidence: 99%
See 3 more Smart Citations